Oxford Textbook of Migrant Psychiatry 2021
DOI: 10.1093/med/9780198833741.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Mental health needs of lesbian, gay, bisexual, and transgender migrants

Abstract: Lesbian, gay, bisexual, and transgender (LGBT) migrants have a unique set of experiences that affect mental health. Many are forced to flee their home countries owing to persecution, and both pre- and post-migration factors can affect their well-being. Mental health providers would benefit from learning about the specific needs of this population. In this chapter, we will discuss LGBT migrant experiences with regard to pre- and post-migration factors affecting mental health. We will address relevant terminolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This correlates with the findings from several studies that indicated that the negative consequences of a lack of SRHS for LGBTQI individuals were understood by the PHC nurses. For example, increased sexually transmitted illnesses like HIV/AIDS, psychological problems like anger and frustration, and social issues, which included corrective rape, death, and gender-based violence [ 35 , 36 , 37 , 38 ]. The significance of public awareness and transparency about LGBTQI SRHS was indicated as one of the vital approaches to improving SRHS at primary healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with the findings from several studies that indicated that the negative consequences of a lack of SRHS for LGBTQI individuals were understood by the PHC nurses. For example, increased sexually transmitted illnesses like HIV/AIDS, psychological problems like anger and frustration, and social issues, which included corrective rape, death, and gender-based violence [ 35 , 36 , 37 , 38 ]. The significance of public awareness and transparency about LGBTQI SRHS was indicated as one of the vital approaches to improving SRHS at primary healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%